Analisis Faktor-Faktor Yang Memengaruhi Kepuasan Pengguna Layanan Go-Ride (Studi Pada Mahasiswa Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Diponegoro) - Septi Puspitasari; Widayanto Widayanto (Universitas Diponegoro, 2019)
This research aims to determine factor which the biggest contribution to satisfaction Go-Ride service users. Satisfaction was measured by five initial factors, service quality, price, perceived ease, perceived usefulness and online servicescape. This type research is explanatory research. The sampling technique non probability sampling with purposive sampling and accidental sampling. Samples taken 100 respondents using Go-Ride services in Undip FISIP. The results showed form five variables with 65 indicators only 24 indicators met the value KMO MSA and can be factor analysis, total variance explaned and rotated component matrix forms three components, hereinafter referred service quality, perceived ease and perceived usefulness, regression test stages shows service quality, perceived ease, perceived usefulness partially and simultaneously have positive and significant influence user satisfaction, perceived usefulness was dominant influence user satisfaction. Researcher suggestions to improve service quality, especially responsiveness service, implementation the most effective route selection according user's wishes, implementation reference coupon strategy.